2023
DOI: 10.3390/coatings13020321
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation into Residual Stress Control of 24CrNiMo Alloy Steel by Selective Laser Melting

Abstract: Residual stresses are a major problem in SLM forming of large-sized parts of high-performance materials. The purpose of this study is to investigate the effects of scanning strategy, preheating temperature, and heat treatment on residual stresses in SLM formed high-strength steels. An experimental method was used to investigate the residual stresses in SLM forming of high-strength steels. The peak and distribution of residual stresses can be changed by optimizing the scanning strategy. The most suitable scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…= wavelength is λ standard whiteboard spectral reflection ratio; ρ = wavelength for λ test site (external wall, roof) relative to the standard whiteboard spectral reflection ratio [1].…”
Section: Whereρmentioning
confidence: 99%
“…= wavelength is λ standard whiteboard spectral reflection ratio; ρ = wavelength for λ test site (external wall, roof) relative to the standard whiteboard spectral reflection ratio [1].…”
Section: Whereρmentioning
confidence: 99%
“…[ 22,23 ] Sudiro et al [ 24 ] reported that CoNiCrAlY coatings with 30 wt% Si and CrSi 2 coatings with 10 wt% Ni were significantly effective for enhancing the corrosion resistance of STBA21 alloy in the gas phase of air (Na 2 SO 4 + 25.7 mass% NaCl). Chen et al [ 25 ] also investigated the effect of Si on the high‐temperature corrosion resistance of the Ni–20Cr– x Si ( x = 0, 1, 3, 5 wt%) cladding layers in a mixed salt (NaCl:KCl:K 2 SO 4 :Na 2 SO 4 = 1:1:1:1, mass ratio) at 600°C and found that the Si addition enhances the stability of Cr 2 O 3 in the mixed salt, and Si enriched in the corrosion layer can effectively prevent the penetration of corrosion media and reduce the depth of the Cr‐depletion zone. Mo was found to be an effective element for enhancing the resistance to corrosion of alloys, especially in chlorine‐containing environments.…”
Section: Introductionmentioning
confidence: 99%